Racial and Gender-Based Differences in COVID-19 - Kopel, Jonathan; Perisetti, Abhilash; Roghani, Ali; Aziz, Muhammad; Gajendran, Mahesh; Goyal, Hemant (Frontiers in Public Health, 2020)
The novel coronavirus disease 2019 (COVID-19) pandemic has become a global health crisis since its first appearance in Wuhan, China. Current epidemiological studies suggest that COVID-19 affects older patients with multiple comorbidities such as hypertension, obesity, chronic lung diseases, diabetes mellitus, and cardiovascular disease with higher severity. The socioeconomic differences and psychological impact of COVID-19 affecting males and females are essential to consider in pandemic mitigation and preparedness. The differences in the incidence and severity of COVID-19 are likely to be multifaceted, depending on various biological, social, and economical factors. Studies have shown that females are less susceptible to acquire viral infections, probably due to increased production of immune cells and antibodies, and reduced cytokine production. Specifically, female patients have a higher macrophage and neutrophil activity compared to males. Female patients also have higher antibody production and response. Furthermore, in-vivo studies of the angiotensin-converting enzyme 2 (ACE2) showed higher expression in the kidneys of male and female patients, which may explain the differences in susceptibility and progression of COVID-19 for male and female patients. However, it remains unknown whether the expression of ACE2 differs in the lungs of male or female patients. Disparities in healthcare access and socio-economic status between ethnic groups may influence COVID-19 rates. Ethnic groups, such as African Americans, have higher levels of diabetes, hypertension, obesity, asthma, and heart disease, which may increase their risk of contracting COVID-19. In addition, ethnic minorities have a lower socioeconomic status, which has been associated with weak cell-mediated immunity. In this article, we examine the current literature on the gender and racial differences among COVID-19 patients and further examine the possible biological mechanisms underlying these differences